Efektivitas Daun Seledri terhadap Penurunan Tekanan Darah pada Penderita Hipertensi di Puskesmas Pembantu Berngam Kota Binjai Tahun 2021 - Irma Handayani; Sri Wahyuni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Hypertension is an increase in blood pressure by providing further symptoms to a target organ including stroke (in the brain), coronary heart disease (in the heart blood vessels) and right ventricular hypertrophy or left ventricular hypertrophy (for the heart muscle). The target organ in the brain is in the form of stroke, hypertension is the main cause of stroke which brings high mortality. Management of hypertension can be managed with non-pharmacological measures such as giving celery leaves. The purpose of the study was to analyze the effectiveness of giving celery leaves to reduce blood pressure in patients with hypertension at the Pembantu Berngam Health Center, Binjai City in 2021. This type of research was a quasi-experimental design with a pretest-posttest control group design with one type of treatment. This study uses an intervention that is giving celery leaves by boiling. The intervention was given once in the morning by giving 100 grams of boiled celery for 5 days. The number of samples of 30 respondents with 15 people as the control group and 15 people in the intervention group were taken by accidental sampling. The results of the average blood pressure before and after giving boiled celery in the treatment group with systolic blood pressure p-value is 0.00, diastolic blood pressure p-value is 0.00. The results of statistical tests using the Wilcoxon test for both systolic and distolic pressure in the group not given celery were tilapia p-value > 0.05, namely systolic pressure p-value 0.07 and distolic p-value 0.05. The results of the Mann Whitney U statistical test analysis for systolic and distolic blood pressure obtained a p-value of 0.047 and a diastolic pressure p-value of 0.01 or a p-value <0.05, which means that there is an effectiveness of giving celery leaves in reducing blood pressure in hypertensive patients at the Berngam Binjai sub-health center. It is hoped that health workers will be able to apply complementary therapy to patients with hypertension in maintaining and lowering blood pressure.